Variation of Density and Biomass of the Ichthyofauna Associated to Soft Bottoms of a Western Coastal Lagoon of B.C.S., Mexico: A Recent Study - Castillo-Rosas, Bruma R.; Barjau-González, Emelio; López-Viva, Juan Manuel; Armenta-Quintana, José Ángel; Aguilar-Parra, Javier; Aispuro-Felix, Elvia E. (Research Aspects in Biological Science Vol. 3, 2022)
An assessment of the variation in density and biomass of the fish communities of the lagoon of La Paz, Mexico was conducted from November 2016 to September 2017. A total of 2763 organisms were collected with a total biomass of 211,422.93 g in an area of 5022 m2, a density and biomass of 0.550 lnd/m2 and 44.091 g/m2. The site with the largest biomass was recorded in Zacatecas (11.179 g/m2) located north of the lagoon, while Grand Plaza recorded the lowest biomass (2.732 g/m2). Regarding the density, the maximum value was recorded in the site Yate Hundido, located northwest of the lagoon (0.129 lnd/m2) and the lowest was Las Palmas (0.036 lnd/m2) located north of the lagoon. Diapterus peruvianus was the most abundant species, with 683 individuals and a biomass of 37,507.57 g. The physicochemical factors revealed two seasons with significant fluctuation, with greater temperatures in the summer (average of 27.45°C.) and lower temperatures in the winter (average of 22.49°C.). The Shannon-Weaver diversity index demonstrated a difference between months (p = 0.050), with the maximum value (H' = 2.133 bits/ind) in April and the lowest value (H' = 1.041 bits/ind) in June. The general objective was to determine the biomass and density of the resident and transitory fish species of the La Paz lagoon, finding that the values of biomass and density recorded in the lagoon were found to be associated with the spatio-temporal variation of the temperature of the lagoon, as well as with the resident and transient species located in the study area.